SNP discovery from liver transcriptome in the fish Piaractus mesopotamicus - Mastrochirico-Filho, Vito Antonio [UNESP]; Hata, Milene Elissa [UNESP]; Sato, Lucas Seiti [UNESP]; Jorge, Paulo Henrique [UNESP]; Foresti, Fausto [UNESP]; Rodriguez, Manuel Vera; Martínez, Paulino; Porto-Foresti, Fábio [UNESP]; Hashimoto, Diogo Teruo [UNESP] (Springer Nature, 2016)
Pacu (Piaractus mesopotamicus) is a Neotropical freshwater fish threatened by overfishing, and one of the species of highest commercial value for aquaculture. Genetic variability analysis through molecular markers is an essential technique to genetic management of the wild and cultivated stocks. The main objective of this study was to identify and validate gene-associated SNPs of the liver transcriptome of pacu. Through genetic analysis in one natural population (Paraná River), 32 polymorphic SNPs were successfully genotyped and validated, some of them related to immune system genes. The observed and expected heterozygosity ranged from 0.059 to 0.706 and 0.058 to 0.507, respectively. All loci were in Hardy–Weinberg equilibrium (P > 0.05). Our results showed useful genomic resources for pacu, with applicability in conservation purposes and aquaculture industry by using SNPs markers.
Keywords: Aquaculture; Genetic variability; NGS; Pacu